2017
DOI: 10.1111/ases.12445
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic colectomy after self‐expanding metallic stent placement through the ileocecal valve for right‐sided malignant colonic obstruction: A case report

Abstract: A 78-year-old man with a history of open sigmoidectomy for sigmoid cancer presented with abdominal pain and vomiting. Abdominal multi-detector CT revealed an obstructive ileocecal tumor with distended small bowel on the oral side. We performed emergency drainage using a transnasal decompression tube, and 2 days later, we conducted a colonoscopic examination, which lead to a provisional diagnosis of obstruction with a malignant tumor invading the ileocecal valve. We then placed a self-expanding metallic stent (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…However, recent studies have concluded that preoperative decompression using SEMS and transanal drainage tube is helpful when performing subsequent elective laparoscopic surgery and one-stage anastomosis [8]. Preoperative decompression of the distended bowel increases intraabdominal working space during surgery and reduces bowel edema, leading to greater safety during one-stage anastomosis [1, 9].…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have concluded that preoperative decompression using SEMS and transanal drainage tube is helpful when performing subsequent elective laparoscopic surgery and one-stage anastomosis [8]. Preoperative decompression of the distended bowel increases intraabdominal working space during surgery and reduces bowel edema, leading to greater safety during one-stage anastomosis [1, 9].…”
Section: Discussionmentioning
confidence: 99%